2008
DOI: 10.1152/japplphysiol.01002.2007
|View full text |Cite
|
Sign up to set email alerts
|

Design of a new variable-ventilation method optimized for lung recruitment in mice

Abstract: Variable ventilation (VV), characterized by breath-to-breath variation of tidal volume (Vt) and breathing rate (f), has been shown to improve lung mechanics and blood oxygenation during acute lung injury in many species compared with conventional ventilation (CV), characterized by constant Vt and f. During CV as well as VV, the lungs of mice tend to collapse over time; therefore, the goal of this study was to develop a new VV mode (VV(N)) with an optimized distribution of Vt to maximize recruitment. Groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 56 publications
5
60
2
Order By: Relevance
“…5 In animal models of ARDS, variable ventilation strategies are superior to conventional control mode mechanical ventilation (CMV) or CMV with recruitment maneuvers with respect to lung mechanics, gas exchange, surfactant content, and inflammatory mediators with an overall decrease in distending stress. [5][6][7][8][9][10][11][12] In a recent computed tomography (CT) imaging study, we confirmed BVV induced recruitment of both poorly and non-aerated lung regions. 13 In this study, we hypothesized that the recruitment benefit and periodic low V T breaths seen with BVV could result in enhanced resolution of edema fluid in ARDS.…”
supporting
confidence: 76%
“…5 In animal models of ARDS, variable ventilation strategies are superior to conventional control mode mechanical ventilation (CMV) or CMV with recruitment maneuvers with respect to lung mechanics, gas exchange, surfactant content, and inflammatory mediators with an overall decrease in distending stress. [5][6][7][8][9][10][11][12] In a recent computed tomography (CT) imaging study, we confirmed BVV induced recruitment of both poorly and non-aerated lung regions. 13 In this study, we hypothesized that the recruitment benefit and periodic low V T breaths seen with BVV could result in enhanced resolution of edema fluid in ARDS.…”
supporting
confidence: 76%
“…Because bubble CPAP is compared with conventional ventilator CPAP, 12-15 the therapy's merits have been attributed to the oscillatory component and its ability to exploit nonlinear properties of the lung, inducing phenomena such as stochastic resonance that requires a nonlinear dynamic system (the lung), weak biological signal (CPAP), and superimposed noise (pressure oscillations). 5 The connection was made by Suki and colleagues [16][17][18] while studying variable ventilation in computer simulations and rodent models of acute lung injury. The noise in the pressure signal produced by the bubbling takes advantage of the nonlinearity of atelectatic regions of the lung by exploring higher volume values while mean pressure remains the same; these increases in volume are indicative of additional recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,18,20 A major limitation is that an in vitro model does not allow reliable correlations to patients due to its simplicity. Furthermore, our study did not have a leak in the system, so the oscillations will attenuate more than anticipated from the results in a realistic setting.…”
Section: Limitationsmentioning
confidence: 99%
“…For variable ventilation, the FlexiVent was preprogrammed to deliver a range of V T . The V T distribution used an algorithm that was developed previously to optimize alveolar recruitment in mice (26). Briefly, the distribution of V T above the most frequently applied V T was followed by a power law decay up to the maximum V T .…”
Section: Ventilation Protocolmentioning
confidence: 99%